2021
DOI: 10.1186/s41747-021-00206-4
|View full text |Cite
|
Sign up to set email alerts
|

CT-derived sarcopenia should not preclude surgical stabilization of traumatic rib fractures

Abstract: Background Rib fractures are associated with considerable morbidity and mortality. Surgical stabilization of rib fractures (SSRF) can be performed to mitigate complications. Sarcopenia is in general known to be associated with poor clinical outcomes. We investigated if sarcopenia impacted number of days of mechanical ventilation, intensive care unit (ICU) stay, and total hospital stay in patients who underwent SSRF. Methods A retrospective single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Three additional studies were identified through manual reference review. Finally, we selected 17 studies [ 7 , 18 20 , 29 41 ] that met our criteria for inclusion in the present systematic review and meta-analysis. The study selection flowchart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three additional studies were identified through manual reference review. Finally, we selected 17 studies [ 7 , 18 20 , 29 41 ] that met our criteria for inclusion in the present systematic review and meta-analysis. The study selection flowchart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 17 included studies are summarized in Table 1 . Of these, 3 adopted a prospective cohort study [ 30 , 36 , 38 ], 13 were retrospective cohort study [ 7 , 19 , 20 , 29 , 31 35 , 37 , 39 41 ], and 1 was a cross-sectional study [ 18 ]. The sample sizes for the included studies ranged from 45 to 519, with 3582 total patients and an average age ranging from 41.4 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations